Ultrasonographic Features, Nodule Size, Capsular Invasion, and Lymph Node Metastasis of Solitary Papillary Carcinoma of Thyroid Isthmus - Luo, Honghao; Yan, Feng; Lan, Lin; Ma, Buyun; Zhao, Haina; He, Yushuang; Peng, Yulan (Frontiers in Oncology, 2020)
Objective: The purpose of this retrospective study is to analyze the ultrasound characteristics of solitary papillary thyroid carcinoma (PTC) located in the thyroid isthmus, the risk factors for lymph node (LN) metastasis and capsular invasion. Methods: We included a total of 135 patients of solitary PTC located in the thyroid isthmus. All the patients underwent Ultrasound exam, and the routine total thyroidectomy, and prophylactic central LN dissection. Patient's demographics as well as thyroid isthmus nodule's ultrasound characteristics, risk factors associated with LN metastasis and capsular invasion were analyzed. Results: Based on the postoperative clinicopathological analysis, the occurrence of LN metastasis was higher in male than in female (p < 0.001). As risk factors, the size of isthmus PTC associated to LN metastasis and the capsular invasion were p=0.005 and p=0.000, respectively. The area under the ROC curve (AUC) of the size of isthmus PTC was 0.64 (95% CI: 0.55, 0.72), indicating probability for LN metastasis. The capsular invasion was 0.77 (95% CI: 0.68, 0.83). When the threshold was set at 1.1 cm, the larger size was indicated that there was probably an occurrence of LN metastasis with the sensitivity and specificity of 47.4% and 73.7%, respectively. When the threshold was set 0.7 cm, the larger size indicated that there was potentially a capsular invasion, with the sensitivity and specificity of 80.6% and 56.3%, respectively. Wider-than-tall nodules were found to be significantly different from those in LN metastasis and capsular invasion (p=0.038 and p=0.030, respectively). There were significant differences in capsular invasion in extra-thyroidal extension (ETE) compared with smooth or ill-defined and lobulated or irregular nodule (p=0.017). Conclusions: This study showed that the incidence of LN metastasis in male was higher than that in female. When the ultrasound image shows a thyroid isthmus nodule with a wider-than-tall shape, LN metastasis and capsular invasion were likely to occur. When the ultrasound image shows a thyroid isthmus nodule with an ETE, capsular invasion was likely to occur. ETE and wider-than-tall may be an indicator of FNA under ultrasound guidance, even though the size of thyroid isthmus nodule may be less than 1 cm.